GURU HUMANIS DALAM PENDIDIKAN ISLAM - Musthofa Rahman (Jurnal Pendidikan Islam, 2013)
This paper aims to unravel the humanistic values in Islamic education because dehumanistic attitudes and behaviors often harm the education. In Bima, West Nusa Tenggara, a teacher bear to hit two of his students so that both students had Suffered from head injuries. This condition requires the teaching paradigm to be reconstructed in order that the missions of education can be reached. This study used content analysis as the method to criticize literatures related to humanism. In the context of Islamic education, teachers are muaddib that prepare students to build civilization in the future. Teachers in teaching activities have serial relationships to God (Surah al-'Alaq [96]: 4). They play their roles and functions as role model, facilitator, motivator, and partner in learning for their students. In giving guidance (irshad) the teachers acts as a guide, advisor and mentor. Teacher assists the students to create an environment that does not preclude the development of self-learners naturally.